Modulation of Speech-in-Noise Comprehension through Transcranial Current Stimulation with the Phase-Shifted Speech Envelope - Kadir, Shabnam; Kaza, Chrysoula; Weissbart, Hugo; Reichenbach, Tobias (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2020)
Neural activity tracks the envelope of a speech signal at latencies from 50 ms to 300 ms. Modulating this neural tracking through transcranial alternating current stimulation influences speech comprehension. Two important variables that can affect this modulation are the latency and the phase of the stimulation with respect to the sound. While previous studies have found an influence of both variables on speech comprehension, the interaction between both has not yet been measured. We presented 17 subjects with speech in noise coupled with simultaneous transcranial alternating current stimulation. The currents were based on the envelope of the target speech but shifted by different phases, as well as by two temporal delays of 100 ms and 250 ms. We also employed various control stimulations, and assessed the signal-to-noise ratio at which the subject understood half of the speech. We found that, at both latencies, speech comprehension is modulated by the phase of the current stimulation. However, the form of the modulation differed between the two latencies. Phase and latency of neurostimulation have accordingly distinct influences on speech comprehension. The different effects at the latencies of 100 ms and 250 ms hint at distinct neural processes for speech processing.
CRIS-Team Scopus Importer:2021-02-25
Keywords: speech envelope; speech-in-noise comprehension; Transcranial current stimulation